How Compliance of Surfaces Affects Ankle Moment and Stiffness Regulation During Walking - Xie, Kaifan; Lyu, Yueling; Zhang, Xianyi; Song, Rong (Frontiers in Bioengineering and Biotechnology, 2021)
Human can regulate ankle moment and stiffness to cope with various surfaces during walking, while the effect of surfaces compliance on ankle moment and stiffness regulations remains unclear. In order to find the underlying mechanism, ten healthy subjects were recruited to walk across surfaces with different levels of compliance. Electromyography (EMG), ground reaction forces (GRFs) and three-dimensional reflective marker trajectories were recorded synchronously. Ankle moment and stiffness were estimated using an EMG-driven musculoskeletal model. Our results showed that the compliance of surfaces can affect both ankle moment and stiffness regulations during walking. When the compliance of surfaces increased, the ankle moment increased to prevent lower limb collapse, and the ankle stiffness increased to maintain stability during the mid stance phase of gait. Our work improved the understanding of gait biomechanics and might be instructive to prostheses-assisted walking.